Emerge - Tan, JiaJin (2018)
This report is with reference to the Final Year Project, titled ‘Emerge’. Emerge is a 2D digitally animated short film that tells the story of an individual named ‘Zero’, a lonely individual living among shapeshifters, and his journey towards self-discovery.